KDR inferred haplotype is associated with upper limb dysfunction in breast cancer survivors of mixed ancestry - Mafu, Trevor S (Cancer Manag Res, 2019)
Introduction: Shoulder pain and disability are well-documented sequelae of breast cancer treatment. Angiogenesis signaling may have a role in the development of shoulder pain or shoulder disability in breast cancer survivors. The aim of this study was to determine if polymorphisms in angiogenesis-related genes are associated with shoulder pain or disability following breast cancer treatment. Participants and methods: A cross-sectional study was conducted on 220 South African breast cancer survivors. The study aimed to evaluate associations between shoulder pain/disability and seven single nucleotide polymorphisms (SNPs) within five angiogenesis-associated genes: KDR (rs2305948 C>T; rs7667298 C>T), NOS3 (rs1549758 C>T), MMP2 (rs708269 A>T), THBS2 (rs9766678 A>G) and TIMP3 (rs5754312 T>A; rs715572 G>A). In addition, associations between shoulder pain/disability and inferred haplotypes for KDR and TIMP3 SNPs were evaluated. Participants were grouped into no–low and moderate–high shoulder pain/disability based on total pain/disability scores: ≤30 and >30, respectively using the shoulder pain and disability index (SPADI). Results: No independent associations with shoulder pain/disability categories were found for all SNPs. However, 1 inferred haplotype (KDR “TT”) differed significantly (P=0.014) between the shoulder disability categories. After adjusting for participants’ age, the differences in KDR inferred haplotype frequencies between shoulder disability categories became non-significant (P=0.052). Conclusion: Our findings provide a preliminary suggestion of a possible association between polymorphisms in genes involved in angiogenesis and the presence of moderate–high shoulder disability among South African breast cancer survivors. A larger prospective cohort study is currently being conducted by our group.